Organizational-pedagogic technology of formation of motor functioning culture as mean of physical fitness improvement of 5 form - Deineko, A.H. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to analyze influence of organizational-pedagogic technology of formation of motor functioning’s culture of five form pupils in process of physical education; to test experimentally methodic of formation of motor functioning’s culture by means of general gymnastic in physical education system of comprehensive schools’ pupils. Material: The research was conducted in comprehensive school № 67, Kharkov. 57 pupils of five forms (5-А form - 30 pupils, 5-B - 27 pupils) participated in the research. Results: we worked out organizational-pedagogic technology of formation of motor functioning’s culture “Main gymnastic at school”, which positively influenced on development of physical fitness of experimental groups’ pupils. Conclusions: it was established that under influence of selected exercises of main gymnastic and introduced competitiveness elements pupils’ movements became more accurate, plastic, acquired higher amplitude, coordination.